Incidence of iron deficiency Anaemia during pregnancy in Far North Queensland. (2nd November 2022) - Carter, Edward; Lane, Katie; Ryan, Elizabeth; Jayaratnam, Skandarupan
Abstract: Introduction: The WHO estimates the incidence of iron deficiency anaemia in Australia is 25%. However there is considerable variation during pregnancy and in regional areas. Objective: The aim of this investigation is to quantify the incidence of iron deficiency anaemia during pregnancy within Far North Queensland. Design: This is a single‐centre retrospective cohort study. Cairns Hospital is the main referral centre for complex maternity care in Far North Queensland with an estimated population of 280‐000, which includes many people from rural and remote communities and a high proportion who identify as Aboriginal or Torres Strait Islander. This study included all births at the Cairns Hospital in 2018, a total of 2190 deliveries. Findings: The study randomly sampled 551 mothers from the cohort, and the incidence of iron deficiency anaemia was 34.9%. 48.7% of women who identified as Aboriginal or Torres Strait Islander within the region were anaemic. This was significantly higher than an incidence of 28.9% for the rest of the population. Other risk factors include booking appointment after 28‐weeks, Asian ethnicity and age less than 25‐years. A BMI greater than 35 was protective Discussion: This study will inform antenatal care providers within the region and improve obstetric outcomes by increasing awareness. Identifying risk factors will also facilitate prompt treatment and improve maternity care for vulnerable patient groups. On a broader level, the study provides new data to inform population health estimates both nationally and internationally. Conclusion: The incidence of iron deficiency anaemia during pregnancy in Far North Queensland is significantly higher than previous estimates.